Inflammation-induced endothelial dysfunction involves reduced nitric oxide bioavailability and increased oxidant stress. - Clapp, B; Hingorani, A; Kharbanda, R; Mohamed-Ali, V; Stephens, J; Vallance, P; MacAllister, R (2004)
OBJECTIVES: Our aim was to investigate mechanisms of inflammation-induced endothelial dysfunction in humans. METHODS: Endothelial function in twenty-one healthy human volunteers was measured using forearm venous plethysmography before and 8 h after administration of typhoid vaccination to generate an inflammatory response. Basal and stimulated endothelial nitric oxide (NO) bioavailability was assessed by measurement of the responses to intra-arterial N(G)-monomethyl-l-arginine (l-NMMA) and bradykinin, respectively. The effects of supplementation with l-arginine or ascorbic acid were assessed to probe the effects of substrate deficiency and oxidative stress, respectively. Systemic effects were determined by measuring cytokine response, total anti-oxidant status (TAOS) and urinary protein excretion. RESULTS: Vaccination induced a cytokine response, a fall in total anti-oxidant status and increased urinary albumin excretion (UAE). There was a reduction in the response to bradykinin (BK, P<0.005) and l-NMMA (P<0.0001) with no effect on the response to glyceryl trinitrate (GTN) and norepinephrine (NE). Following vaccination blood flow response to BK (but not GTN) was partially returned to pre-vaccine levels by infusion of ascorbic acid (P=0.01). Supplementation with l-arginine had no effect. CONCLUSION: Inflammation causes widespread endothelial dysfunction, reduces vascular NO bioavailability and increases oxidative stress. These actions are partially reversible with local anti-oxidants. These findings suggest a role for reactive oxygen species in inflammation-induced endothelial dysfunction.